2010
DOI: 10.1262/jrd.09-139s
|View full text |Cite
|
Sign up to set email alerts
|

Expression of VEGF and Its Receptors in the Bovine Endometrium Throughout the Estrous Cycle: Effects of VEGF on Prostaglandin Production in Endometrial Cells

Abstract: Abstract. Vascular endothelial growth factor (VEGF) is a well known angiogenic factor that has been suggested to play some physiological roles in reproductive organs. To clarify whether VEGF is involved in regulating bovine endometrial function locally, in experiment 1, we determined the expression of VEGF, VEGF receptor (VEGFR) 1 and VEGFR2 throughout the estrous cycle in endometrial tissues. Endometrial tissue was collected at estrus (Day 0), the early I (Days 2-3), early II (Days 5-6), mid and late luteal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 41 publications
0
20
1
2
Order By: Relevance
“…In the mare, VEGF, VEGFR1 and VEGFR2 together facilitate the development of maternal and fetal vascular networks for the interchange of gases, nutrients and waste products throughout gestation [24]. In the bovine endometrium, VEGF and its receptors were regulated throughout the estrous cycle [25]. A study in the rhesus monkey during early pregnancy also indicated that VEGF-VEGFR pairs were involved in the process of trophoblast invasion, maternal vascular transformation and fetoplacental vascular differentiation and development [26].…”
Section: Discussionmentioning
confidence: 99%
“…In the mare, VEGF, VEGFR1 and VEGFR2 together facilitate the development of maternal and fetal vascular networks for the interchange of gases, nutrients and waste products throughout gestation [24]. In the bovine endometrium, VEGF and its receptors were regulated throughout the estrous cycle [25]. A study in the rhesus monkey during early pregnancy also indicated that VEGF-VEGFR pairs were involved in the process of trophoblast invasion, maternal vascular transformation and fetoplacental vascular differentiation and development [26].…”
Section: Discussionmentioning
confidence: 99%
“…those that encoded for growth factors/ cytokines or those involved in the progression of the estrous cycle. The expression of insulin-like growth factor 2; IGFII, insulin-like growth factor binding protein 2, 36 kDa; IGFBP2 [48], prostaglandin E receptor 2 (subtype EP2), 53 kDa; PTGER2 [49], vascular endothelial growth factor receptor 2; VEGFR2 [50] in the endometrium, increases during the elongation stage of conceptus development while the expression of ESR1 [51], matrix metallopeptidase 2 (gelatinase A, 72 kDa type IV collagenase; MMP2 [52], and VEGF [50] declines. Treatment with exogenous progesterone increased the expression of uterine serpins [53] as well as PGR, ESR1 and retinol binding protein 4, plasma; RBP4 [54].…”
Section: Cycle Related Changesmentioning
confidence: 99%
“…The expression of some cytokines, growth factors and their receptors by endometrial cells are regulated by ovarian steroidal hormones (Robertson, 2007, Guzeloglu-Kayisli et al, 2009. Within the targeted transcripts, an angiogenic cytokine such as VEGF is up-regulated during oestrus, enabling higher endometrial blood flow, angiogenesis and vascularization as required for endometrial growth during the proliferation and differentiation of epithelial and stromal cells (Tasaki et al, 2010). Likewise, a pro-inflammatory cytokine mediator PTGS2 is up-regulated during late luteal phase as a precursor for PGF2 synthesis from arachidonic acid (AA), playing a role in the initiation of luteolysis (Skarzynski et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The repair mechanism also includes a remodelling of the vasculature and restoration of oxygen to the hypoxic tissue. The phagocytosis of apoptotic neutrophils by macrophages stimulates the secretion of VEGF, which enhances tissue angiogenesis, revascularisation and wound repair (Tasaki et al, 2010).…”
Section: Effects Of Endometrial Sampling On Uterine Healthmentioning
confidence: 99%
See 1 more Smart Citation